Jan ze Trzciany`s reflections over the concept of human dignity in "De Natura Ac Dignitate Hominis", 1554 = Jana ze Trzciany koncepcja godności człowieka zawarta w pracy "De Natura Ac Dignitate Hominis", 1554 - Glabinska Kelly, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article sheds light on an important aspect of Polish and European history of thought; namely, how ideas of the humanist movement that were born in Renaissance Florence spread to western and central Europe, being adopted at various universities north of the Alps. The specific notion of human dignity in Polish Renaissance philosophy influenced ideas of tolerance and enriched the political and philosophical debate in Poland.
Keywords: human dignity; Polish Renaissance; Renaissance philosophy; Jan of Trzciana (ca 1510-1567); Arundinensis; humanist movement; human rights; godność ludzka; renesans polski; filozofia renesansowa; Jan z Trzciany (ok. 1510-1567); prawa człowieka